Evaluation of the efficiency of bamboo-based biochar adsorption in the removal of formaldehyde in air. - Mijares, Miguel Paulo Deluao
Formaldehyde (CH2O) is a hazardous volatile compound (VOC) that is usually found in indoor environments, coming from various sources like furniture, paints, plastic covers, and other household materials. High levels of this pollutant may cause various health conditions from irritation in the eyes and nose to severe damages to the respiratory system. Hence, there is a need for the removal of CH2O from indoor areas to maintain good indoor air quality, as well as ensuring human health. This study produced biochar from bamboo shavings waste (BSW) from furniture enterprises and evaluated its efficiency in removing CH2O from air. The BSW biochar was characterized using SEM and FTIR to determine its morphology and the present functional groups. The significance of varying parameters such as pollutant concentration, adsorbent amount and contact time were evaluated in the adsorption process. Results showed that the percent removal (%) of formaldehyde increased with increasing adsorbent loading due to more available active sites for capture. Similarly, increasing the time of contact increased the opportunity for interaction between the adsorbent and formaldehyde molecules, thus leading to an increase in the removal. The adsorption mechanism was best described by the pseudo-first order as it had the highest correlation coefficient (R2). The adsorption mechanism occurred in two stages, from bulk of pollutant molecules to the external film of the adsorbent, and then intraparticle diffusion (IPD) where it was found out that that IPD was not the only rate-limiting step. Overall, the BSWB was found to have great potential in removing formaldehyde in air at harmful concentration levels with a percent removal range of 37% to 47%.